PENGARUH KUALITAS PELAYANAN TERHADAP MOTIVASI DAN LOYALITAS MAHASISWA UNIVERSITAS DARUNNAJAH - Fazrina S, Rizka; Jalaludin, Engga; Nurmajdina (Media Mahardhika, 2025)
Improving service quality, motivation, and student loyalty is a crucial aspect in ensuring the desire of higher education institutions. This study aims to theoretically and empirically test the impact of student perceived service quality (SPSQ), student motivation, and student loyalty. The research approach used is a survey, with data collection on student perceptions of service quality, motivation, and loyalty at Darunnajah University. Data analysis was carried out using Smart-PLS 3.0, involving two stages: first, testing the outer model on six dimensions of service quality perceived by students, including validity, reliability, and discriminant validity tests. Second, testing the structural model and relationships between constructs (Path analysis). Data were obtained through questionnaires distributed to 100 students selected using purposive sampling techniques, with measurement variables using the Likert scale. The results of the study produced a six-dimensional model with 23 items for the service quality variable, and showed a direct positive effect of student perceived service quality on student motivation and loyalty at Darunnajah University.